Evolution of Entering the Caste-based Untouchability System in Nepal (London Journal of Research In Humanities and Social Sciences, 2024)
The early history of Nepal centers around the Kathmandu Valley, believed to have been covered by a water pond in ancient times. Over thousands of years, as the water receded, people settled here, starting with groups of migrants and cow herders known as 'Nepa.' The Gopal and Mahishapal rulers followed, associated with agricultural professions. The Kirata Period followed, marked by warrior Aryan Kiratas who ruled after defeating the Mahishapals. The origin of the Kiratas is debated, with various theories about their entry into Nepal. This period is mentioned in Hindu texts, and it's believed that Kiratas might have a connection with the Ancient Indus civilization. Despite uncertainties, it's agreed that Kiratas ruled Nepal after the Mahishapals. The Kirata era stood out for its egalitarian society, contrasting with later caste systems. Gautama Buddha's time saw the arrival of Shakya refugees. Afterward, various groups, including Licchavi, Koli, and Malla, entered Nepal due to political changes and the rise of Magadha in India. The Lichchavi Period witnessed the development of confederations in the Terai region. Lichchavis eventually defeated the Kirata king, established a caste system, and declared themselves descendants of Surya, Raghu, and Rama. Lichchavis followed Hinduism and enforced caste divisions, leading to a societal shift. This historical journey reveals a Nepal shaped by migrations, changing rulers, and evolving societal structures. The Kirata Period stands as a unique phase of equality, while the Lichchavi Period introduced the caste system. Nepal's history is a complex tapestry, showcasing diverse influences that have contributed to its rich heritage.
Keywords: Auraco Tamed; Lope; indigenous body; Caupolic; hermeneutics.